Kyoṅʻʺ sāʺ ūʺ re khanʻʹ mhanʻʺ khraṅʻʺ, 1980/81 mha 1983/84 a thi - Co Vaṅʻʺ, Ūʺ (Sutesana Ṭhāna, Cīʺ pvāʺ reʺ Takkasuilʻ, 1980)
Estimate of the strength of students in Burma during the academic years 1980/81-1983/84; a research project.